ANALISA PENGARUH BENTUK PIPA KAPILER DAN KECEPATAN PUTAR (RPM) TERHADAP PRODUKTIVITAS MESIN SPINNER PENIRIS MINYAK (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
Spinner machine has become a secondary requirement in major cities. This is because the air temperature continues to rise each year. Spinner machine has the centralpoint in use they can be used as air-conditioning, food preservatives, and others - others.The impact that often occurs in using of cooling machine is continuously increasing the riskof damage to the cooler. Damage often occurs in the compressor of the cooling machine.The compressor itself is the heart of the cooling system. The cause damage to thecompressor is usually due to inhibition of the capillary tube crust. In this study, the writeruses a shape variation of the capillary tube like spirals, triangles, rectangles and evaporatorair velocity of 200, 300, and 400 rpm, but with the same diameter capillary tube which is0,54 mm. Based on the results of research that is conducted the best to form a capillarytube is evaporator spiral with air speed of 300 RPM, it is marked by the largest price ofCOP 10.5. This is due to compression levels fell to 18.6%, the effectiveness of the coolingmachine would rise.Keywords: COP (Coefficient of Performance), effectiveness of the machine, Shape ofcapillary tube